Impact of nonlinearity of the contact layer between elements joined in a multi-bolted system on its preload - Grzejda, Rafał (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with modelling and calculations of asymmetrical multi-bolted joints at the assembly stage. The physical model of the joint is based on a system composed of four subsystems, which are: a couple of joined elements, a contact layer between the elements, and a set of bolts. The contact layer is assumed as the Winkler model, which can be treated as a nonlinear or linear model.
Keywords: multi-bolted joint; systemic approach; assembly state; preload